A Comprehensive Feasibility Study Incorporating Economic Metrics and Performance Dynamics for 100 MW Wind Farm in Al-Fajer Site, Iraq - Abdulwahed, Hassan S.; Mahmood, Faleh H.; Resen, Ali K. (Iraqi Journal of Science, 2025)
Analyzing feasibility studies is essential for enhancing wind farms’ availability, efficiency, and economy during construction and operation. Wind power and other renewable energy sources offer promising prospects for sustainable and cost-effective energy solutions. Considering technical and economic factors, this study evaluates the viability of establishing an onshore wind farm in the Al-Fajer location in southeastern Iraq. The RETScreen expert software is used to conduct financial analyses and assess the potential annual energy generation of the proposed project. The study includes analysis and evaluation using three distinct scenarios: economic factors such as investment costs, operation and maintenance costs, and the increasing debt rate. The second scenario produces the most favorable financial results, with a net present value of 236,505,368 and an internal rate of return of 18.2%.